Fixture Planning for Multi-Workpiece Setup for Make-to-Order Industry - Ma'ruf, Anas; Siregar, Edwin Syalli (Institute of Research and Community Outreach - Petra Christian University, 2024)
An alternative method to reduce setup time is to simultaneously carry out fixture planning for several parts in one setup planning. This is possible due to the size of parts which are relatively small to the size of the machine work bed, typically found in a make-to-order industry. This research proposed a fixture planning method for multi-workpiece setup. The fixture planning method comprised two stages: 1) multi-workpiece layout and 2) 3-2-1 pin location. An example of multiple workpiece setup is illustrated in this paper to point out the method's applicability. Future research activity will integrate the proposed collaborative human-robot assembly design system method.